Online Educational Games-Based Learning in Disaster Management Education: Influence on Educational Effectiveness and Student Motivation - Thangagiri, B.; Naganathan, R. (2016 IEEE Eighth International Conference on Technology for Education (T4E), 2016)
The aim of this study was to measure the learning effectiveness and motivational appeal of an online games for learning Disaster Management Education (DME) concepts, which was designed according to the curricular objectives and the subject matter of the Mepco Schlenk Engineering College (MSEC) curriculum, as compared to a similar application, encompassing equal learning objectives and content but lacking the gaming aspect. The study also investigated prospective gender differences in the game's learning efficacy and motivational appeal. The sample was 124 students, who were arbitrarily apportioned to two groups, one of which used the online gaming application (Group A, N = 62) and the other one the non-user of online gaming one (Group B, N = 62). A Disaster Management Knowledge Test (DMKT) was used as the pre-test and post-test. Students were also perceived during the interventions. Data analyses disclosed that the gaming approach was both more active in stimulating students' knowledge of DME concepts and more motivational than the non-online gaming approach. Despite girls' greater involvement with, liking of and experience in disaster online gaming, and their greater initial disaster management knowledge, the learning gains that boys and girls achieved through the usage of the game did not differ significantly, and the game was found to be more motivational for girls than the boys. The results suggest that within MSEC, online educational disaster management games can be exploited as effective and motivational learning environments, irrespective of students' gender.